(untitled) (Clinics, 2012)
Primary hyperparathyroidism associated with multiple endocrine neoplasia type I (hyperparathyroidism/multiple endocrine neoplasia type 1) differs in many aspects from sporadic hyperparathyroidism, which is the most frequently occurring form of hyperparathyroidism. Bone mineral density has frequently been studied in sporadic hyperparathyroidism but it has very rarely been examined in cases of hyperparathyroidism/multiple endocrine neoplasia type 1. Cortical bone mineral density in hyperparathyroidism/multiple endocrine neoplasia type 1 cases has only recently been examined, and early, severe and frequent bone mineral losses have been documented at this site. Early bone mineral losses are highly prevalent in the trabecular bone of patients with hyperparathyroidism/multiple endocrine neoplasia type 1. In summary, bone mineral disease in multiple endocrine neoplasia type 1related hyperparathyroidism is an early, frequent and severe disturbance, occurring in both the cortical and trabecular bones. In addition, renal complications secondary to sporadic hyperparathyroidism are often studied, but very little work has been done on this issue in hyperparathyroidism/multiple endocrine neoplasia type 1. It has been recently verified that early, frequent, and severe renal lesions occur in patients with hyperparathyroidism/multiple endocrine neoplasia type 1, which may lead to increased morbidity and mortality. In this article we review the few available studies on bone mineral and renal disturbances in the setting of hyperparathyroidism/multiple endocrine neoplasia type 1. We performed a meta-analysis of the available data on bone mineral and renal disease in cases of multiple endocrine neoplasia type 1-related hyperparathyroidism.